Fear and Uncertainty Do Not Influence Reported Willingness to Undergo Lumbar Punctures in a U.S. Multi-Cultural Cohort - Tsvetkova, Dobromira Z. (Front Aging Neurosci, 2017)
Cerebrospinal fluid (CSF) biomarkers for Alzheimer’s disease and related disorders can provide early and accurate prediction of underlying neuropathology even when the clinical symptoms are mild, but lumbar punctures (LP) to obtain CSF can be perceived as frightening and invasive. We previously demonstrated that this negative perception of the LP is strongly associated with a negative LP experience in terms of discomfort and complications, but it is not known what factors can lead to a negative perception of the LP. It has also been proposed that LP is less well-perceived by adults in the U.S. compared to Europe and elsewhere, although there is a paucity of primary data to support this. To address these knowledge gaps, we conducted a survey of 237 younger and older adults in the Atlanta area including a significant number born outside of the U.S. (n = 82, 34%) to determine demographic, medical, and experiential factors associated with the perception of LP as well as the willingness to undergo LP for medical or research purposes. Our results show that one in four respondents in this cohort with limited first-hand LP experience viewed the LP as a frightening invasive procedure, but the majority (89%) were willing to undergo LP for medical reasons. General awareness of the LP was associated with both standard and negative views of the LP, but perception did not influence willingness to undergo the procedure. Multi-variate models showed that higher annual household income, not place of birth or past experience, was associated with greater willingness to undergo LPs. We conclude that Americans (born in the U.S. or abroad) are not resistant to LPs if there is useful information to improve their health, although there is limited enthusiasm to undergo LPs solely for research purposes. At the same time, we failed to find modifiable factors to improve the perception of LP among those who already perceive it as frightening and invasive. Future recruitment effort should target adults with no preconceived notion of the LP with emphasis on data related to safety and tolerability.